Fibroblast growth factor 1 ameliorates thin endometrium in rats through activation of the autophagic pathway - Zhu, Jing; Li, Zhenyao; Yin, Fengli; Yu, Xiaoting; Lu, Yuanfan; Zhou, Tong; Gong, Fanghua; Xu, Zhangye (Frontiers in Pharmacology, 2023)
Background：Thin endometrium is a reproductive disorder that affects embryo implantation. There are several therapies available for this disease, however they are not so effective. Fibroblast growth factor 1 (FGF1) is a member of fibroblast growth factor superfamily (FGFs), and it has been demonstrated that FGF1 expression was altered in samples collected from patients with thin endometrium. However, it is unclear if FGF1 could improve thin endometrium. The aim of this study was to investigate whether FGF1 have a therapeutic effect on thin endometrium. Methods: A model of thin endometrium induced by ethanol was constructed to investigate the effect and mechanism of action of FGF1 in thin endometrium. In the characterization experiments, 6-8 weeks female rats (n=40) were divided into four groups: i) Control group; ii) Sham group; and iii) Injured group; (iv) FGF1 therapy group. Endometrial tissues would be removed after three motility cycles after molding. Morphology and histology of the endometrium were evaluated by visual and hematoxylin and eosin staining. Masson staining and expression of α-SMA in endometrium showed the degree of endometrial fibrosis. Western blotting (PCNA、vWF and Vim) and immunohistochemistry (CK19 and MUC-1) demonstrated the effect of FGF1 on cell proliferation and angiogenesis. Moreover, immunohistochemistry (ER and PR) was used to explore the function of endometrium. The remaining rats were divided into three groups: i) Injured group; ii) FGF1 therapy group; and iii) 3-methyladenine. Western blotting (p38、p-p38、PI3K 、SQSTM1 /p62、beclin-1 and LC3) was used to explore the mechanisms of FGF1. Results: In FGF1 therapy group, the morphology and histology of endometrium improved compared with the model group. Masson staining and the expression level of α-SMA showed that FGF1 could decrease the fibrotic area of endometrium. Besides, changes in ER and PR expression in the endometrium suggested that FGF1 could restore endometrium-related functions. Western blotting and immunohistochemistry revealed that PCNA、vWF、Vim、CK19 and MUC-1 were significantly increased after FGF1 treatment compared with the thin endometrium. In addition, western blotting showed that p38、p-p38、PI3K、SQSTM1 /p62、beclin-1 and LC3 levels were higher in FGF1 group than in the injured group. Conclusions: FGF1 application cured the thin endometrium caused by ethanol through autophagy mechanism.